Direct Synthesis of Few‐Layer Graphene on NaCl Crystals. Issue 47 (2nd November 2015) - Shi, Liurong; Chen, Ke; Du, Ran; Bachmatiuk, Alicja; Rümmeli, Mark Hermann; Priydarshi, Manish Kumar; Zhang, Yanfeng; Manivannan, Ayyakkannu; Liu, Zhongfan
Abstract : Chemical vapor deposition is used to synthesize few‐layer graphene on micro crystalline sodium chloride (NaCl) powder. The water‐soluble nature of NaCl makes it convenient to produce free standing graphene layers via a facile and low‐cost approach. Unlike traditional metal‐catalyzed or oxygen‐aided growth, the micron‐size NaCl crystal planes play an important role in the nucleation and growth of few‐layer graphene. Moreover, the possibility of synthesizing cuboidal graphene is also demonstrated in the present approach for the first time. Raman spectroscopy, optical microscopy, scanning electron microscopy, transmission electron microscopy, and atomic force microscopy are used to evaluate the quality and structure of the few‐layer graphene along with cuboidal graphene obtained in this process. The few‐layer graphene synthesized using the present method has an adsorption ability for anionic and cationic dye molecules in water. The present synthesis method may pave a facile way for manufacturing few‐layer graphene on a large scale. Abstract : Few‐layer graphene is synthesized on cuboidal NaCl crystals via a facile low temperature chemical vapor deposition method. The removal of NaCl substrate can be achieved easily by a water washing process due to its water‐soluble nature. Cuboidal graphene boxes can also be obtained by replicating the morphology of NaCl crystals.